Role of Households’ Religious Beliefs on the Iranian Households’ Utility Using Dynamic Stochastic General Equilibrium Model - Izadi, Hamid Reza (International Journal of Economics, Management and Accounting, 2026)
Since Iran is one of the Muslim countries and in a Muslim country, religious teachings and thoughts play an important role in the consumption and the behavior of economics of households, so, by separating household consumption expenditures into two parts, halal and non-halal consumption expenditures, this article examines halal household consumption expenditures and the effect and share of these expenditures on the utility of community members using the Dynamic Stochastic General Equilibrium (DSGE) model. The findings show that religion and religious thoughts in Muslim-majority societies play an important and influential role in determining the share of the household consumption bundle, and the utility of this group of households is highly dependent on the share of household consumption expenditures on halal goods. The results indicate that religious and pious people manifest a kind of religious-social behavior based on their religious thoughts, which plays an important role in determining the composition and consumption bundle of the household, which in turn helps to improve the country’s economy and expand its institutional capacities in eliminating poverty and optimizing the market.